Long-term exposure to air pollution and mortality from dementia, psychiatric disorders, and suicide in a large pooled European cohort: ELAPSE study. (December 2022) - Andersen, Zorana J.; Zhang, Jiawei; Jørgensen, Jeanette T.; Samoli, Evangelia; Liu, Shuo; Chen, Jie; Strak, Maciej; Wolf, Kathrin; Weinmayr, Gudrun; Rodopolou, Sophia; Remfry, Elizabeth; de Hoogh, Kees; et al.
Graphical abstract: Highlights: Air pollution was not associated with dementia mortality in seven European cohorts. PM2.5, NO2, and BC were positively associated with psychiatric disorders mortality and suicide. O3 was not associated with dementia, psychiatric disorders, and suicide mortality. Abstract: Ambient air pollution is an established risk factor for premature mortality from chronic cardiovascular, respiratory and metabolic diseases, while evidence on neurodegenerative diseases and psychiatric disorders remains limited. We examined the association between long-term exposure to air pollution and mortality from dementia, psychiatric disorders, and suicide in seven European cohorts. Within the multicenter project 'Effects of Low-Level Air Pollution: A Study in Europe' (ELAPSE), we pooled data from seven European cohorts from six countries. Based on the residential addresses, annual mean levels of fine particulate matter (PM2.5 ), nitrogen dioxide (NO2 ), black carbon (BC), ozone (O3 ), and 8 PM2.5 components were estimated using Europe-wide hybrid land-use regression models. We applied stratified Cox proportional hazard models to investigate the associations between air pollution and mortality from dementia, psychiatric disorders, and suicide. Of 271, 720 participants, 900 died from dementia, 241 from psychiatric disorders, and 164 from suicide, during a mean follow-up of 19.7 years. In fully adjusted models, we observed positive associations of NO2 (hazard ratio [HR] = 1.38; 95 % confidence interval [CI]: 1.13, 1.70 per 10 µg/m 3 ), PM2.5 (HR = 1.29; 95 % CI: 0.98, 1.71 per 5 µg/m 3 ), and BC (HR = 1.37; 95 % CI: 1.11, 1.69 per 0.5 × 10 −5 /m) with psychiatric disorders mortality, as well as with suicide (NO2 : HR = 1.13 [95 % CI: 0.92, 1.38]; PM2.5 : HR = 1.19 [95 % CI: 0.76, 1.87]; BC: HR = 1.08 [95 % CI: 0.87, 1.35]), and no association with dementia mortality. We did not detect any positive associations of O3 and 8 PM2.5 components with any of the three mortality outcomes. Long-term exposure to NO2, PM2.5, and BC may lead to premature mortality from psychiatric disorders and suicide.